Liver function and prognosis, and influence of sacubitril/valsartan in patients with heart failure with reduced ejection fraction. (14th May 2020) - Suzuki, Kota; Claggett, Brian; Minamisawa, Masatoshi; Packer, Milton; Zile, Michael R.; Rouleau, Jean; Swedberg, Karl; Lefkowitz, Martin; Shi, Victor; McMurray, John J.V.; Zucker, Stephen D.; Solomon, Scott D.
Abstract : Aims: The prevalence of liver function abnormalities is common in patients with heart failure (HF) with reduced ejection fraction (HFrEF). We assessed the impact of liver function on prognosis and the effect of sacubitril/valsartan on measures of liver function in patients with HFrEF. Methods and results: The PARADIGM‐HF trial was a randomized, double‐blind, active treatment‐controlled trial. We included 8232 HFrEF patients with available measures of liver function, including transaminases, alkaline phosphatase (ALP) and bilirubin; the primary endpoint was a composite of HF hospitalization and cardiovascular (CV) death. At screening, 11.6% of study patients had total bilirubin above the upper limit of normal (20.5 μmol/L) and 9.2% had ALP above the upper limit of normal (123 IU/L). Although ALP and albumin were associated with an increased risk of outcomes, among conventional test of liver function, total bilirubin was the strongest predictor for the primary endpoint [hazard ratio (HR) 1.10; 95% confidence interval (CI) 1.04–1.15; P < 0.001], HF hospitalization (HR 1.14; 95% CI 1.07–1.22; P < 0.001); CV death (HR 1.07; 95% CI 1.00–1.14; P = 0.040), and all‐cause death (HR 1.08; 95% CI 1.02–1.14; P = 0.009). All conventional measures of liver function were significantly improved in the sacubitril/valsartan group compared with the enalapril group after randomization (between‐group reduction: total bilirubin 2.4%, 95% CI 0.7–4.2%, P = 0.007; aspartate aminotransferase 7.9%, 95% CI 6.7–9.0%, P < 0.001; alanine aminotransferase 7.7%; 95% CI 6.2–9.3%, P < 0.001; ALP 5.4%, 95% CI 4.4–6.4%, P < 0.001). Conclusion: Total bilirubin was a significant and independent predictor of CV death or HF hospitalization and all‐cause mortality in patients with HFrEF enrolled in PARADIGM‐HF. Sacubitril/valsartan improved measures of liver function compared with enalapril.